Genetic Variation of Cephalopachus bancanus from Bangka and Belitung Islands Based on Cytochrome-B Marker Gene Analysis - Adinda Diva Shafira; Herlanda Wahid; Hanum Laila (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2026)
The Western tarsier (Cephalopachus bancanus) is a nocturnal primate distributed across Sundaland, including Bangka and Belitung Islands, where populations face increasing habitat disturbance and conservation threats. Geographic isolation may contribute to genetic differentiation between subspecies. Despite their conservation importance, genetic information for these insular populations remains limited. This study investigated the genetic variation and phylogenetic relationships of C. b. bancanus from Bangka Island and C. b. saltatorfrom Belitung Island using partial mitochondrial Cytochrome-B (Cyt-B) sequences. Ear tissue samples were collected from twelve individuals (six from each island), and DNA was amplified using GLUD-GL and CB2H primers. Amplified fragments ranged from 470–479 bp and showed high similarity (≥91%) with reference C. bancanus sequences in GenBank. Sequence alignment identified conserved and variable nucleotide sites, including parsimony-informative characters and singleton mutations. Haplotype diversity was high (Hd = 0.933), indicating substantial mitochondrial variation within the sampled populations. Phylogenetic reconstruction using the Neighbor-Joining method revealed partial clustering according to island origin, although several individuals shared closely related haplotypes across populations. The low level of sequence divergence may reflect historical connectivity between Bangka and Belitung during Pleistocene land bridge formation in Sundaland. These findings provide preliminary molecular evidence of evolutionary connectivity among island populations and emphasize the importance of integrating genetic information into future conservation and management strategies for Cephalopachus bancanus.